Reactivity of ytterbium(ii) silylamide supported by a pyrrolyl–cyclopentadienyl ligand. Issue 2 (13th November 2014) - Li, Jianfeng; Hao, Jingjun; Cui, Chunming
Abstract : Diverse and high reactivity of a divalent ytterbium amide with the labile pyrrolyl π arm has been demonstrated. Abstract : Reactivity of a divalent ytterbium amide LYbN(SiMe3 )2 (1, L = Me4 C5 -SiMe2 -NC4 H4 ) supported by a pyrrolyl functionalized cyclopentadienyl ligand has been investigated. Reactions of1 with the element sulfur led to the oxidation of the ytterbium to yield the disulfide-bridged ytterbium complex [LYbN(SiMe3 )2 ]2 (μ–η 2 :η 2 -S2 ) (2 ) while that with AgBPh4 resulted in the oxidation of the amide ligand to yield the divalent ytterbium complex LYb(BPh4 ) (3 ) along with the formation of silver and the N–N coupling product [N(SiMe3 )2 ]2 . Reactions of1 with phenol, phenylacetylene and aniline led to the formation of the corresponding ytterbium aryloxide [LYb(μ-OAr 1 )]2 (4, Ar 1 = 2, 6- t Bu2 -4-MeC6 H2 ), ytterbium alkynyl complex [LYb(μ-CCAr 2 )]2 (5, Ar 2 = 4- t BuC6 H4 ) and ytterbium amide [(Me4 C5 -SiMe2 -NHAr 3 )Yb(μ-NHAr 3 )]2 (6, Ar 3 = 2, 6-iPr2 C6 H3 ), respectively. The structural analysis of the reaction products revealed that the silyl bridged pyrrolyl arm is not coordinated to the ytterbium center in compounds2, 4 and5 . The formation of6 involved the cleavage of the Si–Npyrrole bond, the same bond cleavage was also observed in the reaction of1 with red phosphorus, leading to the pyrrolide bridged complex [LYb(μ–η 1 :η 5 -NC4 H4 )]2 (7 ).